Analysis of the Determinants of Government Expenditure in Indonesia - Selviana Megawati Sipayung; Paidi Hidayat; M. Syafii (Universitas KH. Abdul Chalim Mojokerto, 2025)
This study aims to identify the influence of economic growth, the Human Development Index (HDI), the Economic Complexity Index (ECI), imports, state debt, and corruption on government spending in Indonesia during the period 1995–2024. Using the Autoregressive Distributed Lag (ARDL) method, this study evaluates the short-term and long-term relationships between these variables. The study results show that economic growth and state debt have a positive and significant effect in the short and long term. The ECI has a significant negative effect on spending, indicating that economic complexity is correlated with fiscal efficiency. The HDI has a positive effect in the short term, but is not significant in the long term. Meanwhile, imports do not show a consistently significant effect. Corruption has a negative impact in the short term, but turns positive and significant in the long term. These findings emphasize the importance of strengthening economic growth, sustainable debt management, improving the quality of human resources, and reforming budget governance to improve the effectiveness of state spending.